Rebusan Daun Kersen (Muntigia Calabura L) Terhadap Penurunan Kadar Gula Darah Pada Pasien Diabetes Mellitus Tipe di Puskesmas Makrayu - Safitri, Serli Wulan; Parmin, Selamat; Saputra, Andre Utama (Yayasan Daarul Huda Kruengmane, 2024)
Type 2 Diabetes Mellitus is a metabolic disorder characterized by increased blood sugar due to decreased insulin secretion by the body's pancreatic beta cells which cannot use the insulin produced effectively. Kersen leaves contain saponins and flavonoids which can inhibit the absorption of blood sugar from the intestines. This research aims to determine whether there is an effect of boiled water from cherry leaves on reducing blood sugar levels. The research design used was quasi-experimental with a research design (two group pretest-posttest design). The research sample was 30 respondents suffering from diabetes mellitus at the Makrayu Community Health Center. Data analysis was carried out using the paired sample t-test. Based on the results of the hypothesis test, the average value of decreasing blood sugar levels between before and after consuming cherry leaf boiled water was 73.26 mg/dl, supported by a significance value (p-value) of 0.00<0.05. It can be interpreted that there is an effect of boiled cherry leaf water on reducing blood sugar levels in diabetes mellitus sufferers at the Makrayu Health Center. The conclusion is that there is a significant effect of boiled cherry leaf water on reducing blood sugar levels in the intervention group. The average decrease was 73.26 with a standard deviation of 28.45 after administering the boiled cherry leaves, whereas in the control group the average decrease was 13.13 with a standard deviation of 37.80.